Contract Management and Performance of Roads Construction Projects in Kenya Urban Roads Authority - Kithinji, Immaculate Makena; Muinde, Mathias Nzomo; Mungania, Agnes (International Journal of Supply Chain and Logistics, 2025)
Purpose: The study sought to establish the influence of contract management on performance of roads construction projects in Kenya Urban Roads Authority. It was anchored in the institutional theory. Methodology: The study adopted descriptive research design. The target population involved the Kenya Urban Roads Authority in the Upper Eastern Region. The total population for the study was 145 staffs. Using Slovin’s formulae and stratified random sampling, the study sample size was determined to be 106 respondents. The study used structured questionnaires to gather primary data. A 10% of the study sample population was used for pilot testing in Kenya urban roads, central region. In the data processing and analysis, the quantitative data collected was analyzed using SPSS version 26 where descriptive statistics, including means, and standard deviations was analyzed. Inferential analysis focusing on correlation analysis and regression analysis was also done. The results were summarized using tables and figures. Findings: The findings indicated that contract management practices had a strong influence on project performance. These findings suggest that improvements in contract management, particularly in feedback mechanisms, compliance, relationship building, and risk management, can significantly enhance the success of road construction projects managed by the Kenya Urban Roads Authority. Unique Contribution to Theory, Practice and Policy: The study demonstrates that contract management measured by contractor collaboration, legal compliance, and risk management together drive better contract performance in road construction projects. It integrates relational, institutional, and risk frameworks to extend contract-management aspects in devolved infrastructure settings. Practically, it offers actionable measures to reduce delays, cost overruns and defects. Lastly, it supports reforms on contract clauses, enforcement, and payment/retention rules to boost accountability and value-for-money.